Three-Dimensional Animation Design for the Local History Animation "The Origins of Banjarmasin City" - Bie, Kalistowen; Daud, Excel; Suliana, I Made; Sabrila, Trifebi Shina; Mambang (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
The preservation of local history in the digital era requires innovative and interesting media, especially for the younger generation. This study documents the process of designing and producing a 3D animated film entitled "The Origin of the City of Banjarmasin" using Blender software. The project development method includes four main stages: historical exploration, pre-production, production, and post-production. The project produced a short animated film consisting of four key scenes that represent the thematic narrative of Banjarmasin's history, starting from life in a river village to its evolution into a modern city. In production, a hybrid approach is used by combining manual 3D modeling and the utilization of asset templates from open source for efficiency. The results of this project show that Blender is an effective tool for creatively visualizing historical content. 3D animation has proven to have strong potential as an educational medium to revitalize and convey local cultural heritage visually, interactively, and attractively to the digital generation. Three-dimensional visualization allows audiences to experience the historical atmosphere more deeply than conventional media, while opening up more engaging and memorable learning opportunities.